Chemical variables affecting the lime requirement determination of tropical peat soils - Husni, M.H.A.; Devi, Shanthi; Manas, A.R.; Anuar, A.R.; Shamshuddin, J. (Taylor & Francis, 1995)
The carboxyl group in humic acid (HA) is the major functional group influencing the soil acidity. The soil pH(H2O), %HA, buffer capacity, milliequivalent (meq) COOH, meq phenolic OH, and meq total acidity/100 g peat are significantly correlated with lime requirement (LR). The LR of peat soils with high soil pH is low regardless of the effect of other variables (%HA, meq COOH, meq phenolic OH, meq total acidity/100 g peat, and buffer capacity). This indicates that the soil pH(H2O) is an important factor influencing the LR of tropical peat soils. Milliequivalent COOH/g HA is inadequate criteria for determining peat soil acidity component as it changes with humification. However, meq COOH/100 g peat (meq COOH/g HA x %HA) is significantly correlated with LR and this implies the importance of %HA as soil acidity component in tropical peat soils. Buffer capacity is significantly correlated with %HA, meq COOH, meq phenolic OH, and meq total acidity/100 g peat. Stepwise multiple regression analysis indicates that pH(H2O), %HA, and buffer capacity are factors influencing the LR of tropical peat soils.